2021
DOI: 10.1016/j.jenvman.2021.112250
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid constrained coral reefs optimization algorithm with machine learning for optimizing multi-reservoir systems operation

Abstract: The continuous growing demand for water, prolonged periods of drought, and climatic uncertainties attributed mainly to climate change mean surface water reservoirs more than ever need to be managed efficiently. Several optimization algorithms have been developed to optimize multi-reservoir systems operation, mostly during severe dry/wet seasons, to mitigate extreme-events consequences. Yet, convergence speed, presence of local optimums, and calculation-cost efficiency are challenging while looking for the glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Surface water reservoirs must be managed more efficiently than ever before due to climatic uncertainties, which may result in increased water demand and prolonged drought if reservoir policy is not adequately publicised and planned for. The CRO and its enhancement techniques were tested in cascading reservoirs using constrained (CCRO) to narrow the search space and reinforcement learning (CCRO-QL) based on machine learning [ 26 ]. Despite the fact that the results showed that the enhancement technique was highly successful in producing optimal reservoir policy, it is also known that the CRO is a new MHA in this field.…”
Section: Other Mhasmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface water reservoirs must be managed more efficiently than ever before due to climatic uncertainties, which may result in increased water demand and prolonged drought if reservoir policy is not adequately publicised and planned for. The CRO and its enhancement techniques were tested in cascading reservoirs using constrained (CCRO) to narrow the search space and reinforcement learning (CCRO-QL) based on machine learning [ 26 ]. Despite the fact that the results showed that the enhancement technique was highly successful in producing optimal reservoir policy, it is also known that the CRO is a new MHA in this field.…”
Section: Other Mhasmentioning
confidence: 99%
“…Nevertheless, a variety of reservoir models that were focused on the optimum reservoir operating policy, in order to obtain the maximum benefits of the reservoir system/best trade-off in reservoir policy, can be summarised from the above-mentioned research works conducted over the last decades. Another popular topic that has only recently been discussed is the incorporation of the hedging policy into hydropower reservoir systems through the use of MHAs [ 25 , 26 ]. Concurrently, simulation or modelling (NN, SVM, ANFIS, etc.)…”
Section: Other Mhasmentioning
confidence: 99%
“…In [47], a quadratic interpolation approach was introduced with a whale optimization algorithm to solve highdimensional global optimization problems. A machine learning technique was combined with a constrained coral reef optimization algorithm to tune multi-reservoir processing [48]. In [49], a local escaping operator and orthogonal learning were utilized to improve the Archimedes optimization algorithm for PEM fuel cell parameter tuning.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, efficient policy searching approach to balance the multi-sectoral tradeoffs associated with reservoir policy (e.g., flood control, water supply, and hydropower production) has been the focus of much research (Salazar et al, 2017). Of relevance, heuristic optimization algorithms have received increasing attention (Ahmad et al, 2014;Wang et al, 2021a), including various recently proposed algorithms (Bashiri-Atrabi et al, 2015;Chong et al, 2021;Emami et al, 2021;Rani et al, 2020). With the rapid improvement of computational intelligence in recent decades, heuristic algorithms provide fast computation, global optimal solutions, and superior generality to translate observed and projected information into action (Giuliani et al, 2015;Wang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%